A Preliminary Study of Control Parameters for Open Furnace Mild Combustion Using CFD - M. M., Noor; Wandel, Andrew P.; T. F., Yusaf (2012)
Pollution regulation and demand for efficient energy have driven the combustion community to work on combustion improvement. Moderate or Intense Low oxygen Dilution (MILD) combustion is one of the best alternative new technologies for clean and efficient combustion. MILD is proven to be a promising combustion technology for industrial applications. This paper studies the design stage for an open furnace with exhaust gas recirculation (EGR) captured from the flue gas. This study uses ANSYS Fluent to simulate and predict the parameters. The study started with 3D furnace with two EGR. Due to incorrect flow, modifications have been made to the EGR inlet and outlet. Finally 3D model with four EGR was developed and was successful in producing the desired flow in the EGR.